Access to reproductive healthcare beyond the territorial borders. The experience of Ireland and the United States of America (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
The experience of women travelling to different territories to obtain an abortion raises complex legal questions due to the numerous rules and principles involved. A comparative analysis of Ireland and the United States serves as a compelling example of how the right to terminate a pregnancy intersects with the right to travel, particularly given that neither country’s constitutional texts explicitly recognise women’s sexual and reproductive freedoms. This context becomes especially intricate given the contemporary paradigm shift introduced by telemedicine in which, instead of women personally seeking reproductive healthcare, abortion pills are now crossing territorial borders via mail services, with all the legal repercussions that this entails.
Keywords: Abortion care; Ireland; United States of America; medication abortion; reproductive health